Separation and purification of mucins and tenascin-C in breast milk of patients and the investigation of the role of mucins and tenascin-C in the inhibition of HIV-1 - Kehoe, Kathleen (Department of Surgery, 2018)
An estimated 36.7 million people were living with HIV in 2015, with 2.1 million newly infected people with HIV in 2015 worldwide. The highest prevalence of HIV in 2015 was in the Eastern and Southern African regions. This highlights the importance for research in this field to further prevent the number of new HIV cases. Mother-to-child transmission of HIV is due to either cell-associated or cell-free virus present in the breast milk of an HIV positive mother. Most often, HIV positive mothers choose to breastfeed their infants due to the nutritional and immunological benefits outweighing that of the risk of HIV transmission. Importantly, approximately 85% of infants do not acquire HIV through daily exposure to breast milk from their HIV positive mothers who are not on ART suggesting that human breast milk has antiviral properties. Previously in our laboratory, MUC1 and MUC4 has been implicated in the inhibition of HIV-1 in an in vitro assay. Furthermore, crude breast milk was tested in this assay showing strong HIV-1 neutralisation. Pasteurisation (80°C for 10 minutes) of both HIV positive and negative breast milk indicated good neutralisation of HIV-1 in our laboratory. Another breast milk protein, tenascin-C (TNC), was recently shown to strongly neutralise HIV-1 in a study performed by another group. Therefore, with this knowledge, this study was employed to firstly compare the antiviral properties of MUC1, MUC4 and TNC. Furthermore, the HIV-1 neutralisation ability of crude breast milk was sought to be investigated along with the investigation of two different pasteurisation methods including 80°C for 10 minutes and 62.5°C for 30 minutes (Holder pasteurisation). Human breast milk was separated into milk fat and skim milk using caesium chloride density gradient ultracentrifugation. MUC1 was purified from the milk fat using gel extraction from a 4-20% sodium dodecyl sulphate polyacrylamide gel. The skim milk was chromatographed on a Sepharose 2B-CL column from which the void volume was collected to purify TNC using gel extraction from a 4-20% sodium dodecyl sulphate polyacrylamide gel. During this purification, a band consisting of MUC1 which adhered to TNC was used to co-purify the MUC1/TNC glycoprotein using gel extraction. MUC1 and TNC were individually purified using gel extraction. MUC4 was not successfully purified and from ELISA data it was concluded that the concentration of MUC4 was below the detectable limit of the ELISA kit. The average concentration of MUC1 was determined to be 307.85 ng/ml, while the concentration of TNC could not be determined due to the majority of absorbance values (450 nm) lying above the upper limit of the curve. The HIV neutralisation of each of the samples was tested in an in vitro HIV-1 assay. This assay utilises a luciferase reporter gene in modified TZM-bl/JC cells using Du422.1 virus derived from clad C of HIV-1. These assays are being performed to assess the antiviral properties of crude and heat treated breast milk and purified MUC1 and TNC separately as well as co-eluted and co-purified MUC1/TNC. The two pasteurisation methods increased the HIV-1 neutralisation when compared to crude breast milk. The HIV-1 neutralisation of these groups were compared with a Kruskal Wallis test and a statistically significant difference was detected among the crude and 62.5°C heat treated breast milk cohorts (Mann-Whitney U, p-value = 0.0021). Furthermore, a statistically significant difference in the HIV-1 neutralization was detected among the 80°C and 62.5°C heat treated breast milk cohorts (Mann-Whitney, p-value = 0.0033). From the data, and the range of IC₅₀ values (50% inhibitory concentration), the HIV-1 potency was deemed the strongest in the 62.5°C heat treated breast milk. This pasteurisation method could potentially be promoted in lower resource settings to decrease mother-to-child transmission of HIV-1. Purified MUC1 and TNC, as well as co-eluted and co-purified MUC1/TNC, was tested in the same neutralization assay in order to compare the HIV-1 potency of these glycoproteins. The difference in HIV-1 neutralisation was not statistically significant among all three groups (Kruskal Wallis, p-value = 0.13). From the range of IC₅₀ values, it was suggested that TNC has a stronger HIV-1 potency when compared to MUC1. Overall, the co-eluted and co-purified MUC1/TNC showed a lower HIV-1 potency when compared to the single, purified glycoprotein. MUC1 and TNC could be purified and cloned to aid in the protection against contracting HIV-1, especially in mother-to-child transmission of HIV-1. Histochemistry and immunohistochemistry was performed on breast tissue sections to investigate the morphology of the cells and the presence of MUC1, MUC4 and TNC respectively. The lactating breast tissue was confirmed to have wide, dilated lumina and vacuolated cytoplasm with neutral and sialomucins. The presence of MUC1, MUC4 (β subunit) and TNC were confirmed in the lactating breast tissue using immunohistochemistry.